Health Information Science at the University of Victoria: The First Ten Years - Protti, D. J. (Methods of Information in Medicine, 1994)
The University of Victoria has the only program in Canada offering a Bachelor of Science degree in Health Information Science. To meet the requirements of the degree, students must complete 40 courses and 4 CO-OP work terms over 4.3 years. The School admits 30 students each September of which 60% are normally female. Seventy-five percent of the students come from British Columbia, ranging in age from 18 to 42 with the average age being 26 years. In addition to recent high school graduates, over 40% have previous degrees or diplomas, and 65% have over 5 years of work experience. The School’s teaching team consists of 5 full-time faculty, 3 professional staff and 4 part-time faculty. The majority of the faculty have health backgrounds, totalling 135 person-years of practising health care experience. As of November 1992, the School had 113 graduates; 75% are employed in British Columbia, 18% are in other parts of Canada and 7% outside the country. Forty-five percent of the graduates work in government departments including community health agencies; 29% work in hospitals; 26% work in management consulting firms, software houses, or computer hardware firms. They work as systems/project analysts, systems consultants, research assistants, planning analysts, system-support staff, trainers/developers and client account representatives. Some are already in senior management positions.
Keywords: Health Informatics; Curriculum; Education; Training